A fluorescent ratiometric sensor based on covalent immobilization of chalcone derivative and porphyrin Zinc for detecting water content in organic solvents - Wang, Xiao-Yu; Niu, Cheng-Gang; Hu, Liu-Yin; Huang, Da-Wei; Wu, Sheng-Quan; Zhang, Lei; Wen, Xiao-Ju; Zeng, Guang-Ming (Sensors and actuators. B, Chemical, 2017)
•A fluorescent ratiometric sensor for water content determination in organic solvents was presented in this paper.•The fluorescence ratio sensor proposed in the paper minimized the influence of measuring external conditions and obtains a more stable signal.•The sensor showed satisfactory selectivity, reproducibility, stability, and fast response time. This paper describes a fluorescent ratiometric sensor for water content determination in organic solvents. Two different compounds, 4′-N, N-dimethylamino-4-methylacryloylamino chalcone (DMC) and 5, 10, 15, 20-tetra-(4-methylacryloylaminophenyl)porphyrin Zinc (TMAPPZn), were synthesized as indicators for fluorescence ratiometric water sensing. DMC is a fluorescence indicator with charge donor parts and acceptor parts and sensitive to solvent polarity and water content. The fluorescence intensity of TMAPPZn is insensitive to the water content lower than 10% (v/v) water content and employed as the reference indicator. The use of TMAPPZn as a reference indicator resulted in a more stable signal due to minimizing the effects of fluctuations of light intensity, fluorophore bleaching, background signal, and so forth. DMC and TMAPPZn were photo-copolymerized on the silanized glass surface to prevent leakage of the fluorescence indicators. Three organic solutions (ethanol, acetone, and tetrahydrofuran) were used to verify the performances of the proposed sensor, and the sensor exhibited a good linearity in the range 0–10% (v/v) water content with detection limits of 0.0097%, 0.011%, and 0.017% for ethanol, acetone, and tetrahydrofuran, respectively. The ratiometric sensor was characteristic of satisfactory reproducibility, reversibility, short response time. The sensing membrane was found to have a lifetime of two month. We carried out preliminary spiking experiments on the actual samples, and the spiked recoveries were of 99.2–102.0%.